Improved Performance of Direct Torque Control of Induction Machine with 3-Level Neutral Point Clamped Multilevel Inverter - Alias, Nor Faezah; Jidin , Auzani; Said, Mohamed Azmi; Abdullah, Abdul Rahim; JOPRI, MOHD HATTA; Rahim, Nor Hidayah (2013)
A 3-Level Neutral Point Clamped (NPC)Multilevel Inverter was implemented to improve the performance of Direct Torque Control (DTC) of Induction Machine. Larger torque ripple and variable switching frequencies are known as the major problems in DTC of induction machine. This paper aims to propose a suitable voltage vector selection to provide better torque regulation and switching frequency which consequently minimize the major problems. A simple switching strategy was proposed using 7-level torque hysteresis and 2-level flux hysteresis controllers to give more options in selecting an appropriate voltage vector, inherently, according the motor operating conditions. The improvements offered were verified through simulations.